Severity of Coronary Artery Disease in Patients with or without Diabetic Retinopathy - Muhammad Saleem (Journal of Rawalpindi Medical College, 2017)
Background: To determine the frequency of diabetic retinopathy in type 2 diabetic patients undergoing angiographic evaluation and compare the severity (Mean vessel score and mean Gensini score) of coronary artery disease in patients with or without diabetic retinopathy.